Identification and Application of BhAPRR2 Controlling Peel Colour in Wax Gourd (Benincasa hispida) - Ma, Lianlian; Liu, Zhengguo; Cheng, Zhikui; Gou, Jiquan; Chen, Jieying; Yu, Wenjin; Wang, Peng (Frontiers in Plant Science, 2021)
Peel color is an important factor affecting commodity quality in vegetables; however, the genes controlling this trait remain unclear in wax gourd. Here, we used two F2 genetic segregation populations to explore the inheritance patterns and to clone the genes associated with green and white skin in wax gourd. The F2 and BC1 trait segregation ratios were 3:1 and 1:1, respectively, and the trait was controlled by nuclear genes. Bulked segregant analysis of both F2 plants revealed peaks on Chr5 exceeding the confidence interval. Additionally, 6,244 F2 plants were used to compress the candidate interval into a region of 179 Kb; one candidate gene, Bch05G003950 (BhAPRR2), encoding two-component response regulator-like protein Arabidopsis pseudo-response regulator2 (APRR2), which is involved in the regulation of peel color, was present in this interval. Two bases (GA) present in the coding sequence of BhAPRR2 in green-skinned wax gourd were absent from white-skinned wax gourd. The latter contained a frameshift mutation, a premature stop codon, and lacked 335 residues required for the protein functional region. The chlorophyll content and BhAPRR2 expression were significantly higher in green-skinned than in white-skinned wax gourd. Thus, BhAPRR2 may regulate the peel color of wax gourd. This study provides a theoretical foundation for further studies of the mechanism of gene regulation for the fruit peel color of wax gourd.